Lessons learned from 4‐year empowering project management with TALAIA OpenPPM. Issue 11 (6th October 2016) - Mas, Antonia; Mesquida, Antoni‐Lluís; Jovanović, Miloš; Barceló, Joan
Abstract: Knowledge and experience are not the only prerequisite for a successful project; a well‐performing team using proper tools and techniques ensures efficient project management. Adequate tool is essential to support decision making in management of any organizational business units. TALAIA OpenPPM is an open‐source solution for managing projects, programs, and portfolios. SM2, founder of TALAIA OpenPPM, after 4 years of experience of the tool implementation in companies from different sectors, came to a conclusion that the successful adoption of the tool is strongly affected with existing maturity level of the project management processes established in the organization. Also, this article derives lessons learned by SM2 in expansion and opening of a new business line in the international market. Abstract : Knowledge and experience are not the only prerequisite for a successful project; a well‐performing team using proper tools and techniques ensures efficient project management. TALAIA OpenPPM is an open‐source solution for managing projects, programs, and portfolios. SM2, founder of TALAIA OpenPPM, after 4 years of experience of the tool implementation in companies from different sectors, came to a conclusion that the adoption of the tool depends on the maturity level of the project management processes established in the organization.